High-fat diet impairs glucose homeostasis by increased p16 beta-cell expression and alters glucose homeostasis of the progeny in a parental-sex dependent manner - Escalona, Rene; Larqué, Carlos; Cortes, Daniela; Vilchis, Ricardo; Granados-Delgado, Emiliano; Sánchez, Abigail; Sánchez-Bringas, Guadalupe; Lugo-Martínez, Haydée (Frontiers in Endocrinology, 2023)
Introduction Obesity consists in the accumulation of adipose tissue accompanied by low grade chronic inflammation and is considered a pandemic disease. Recent studies have observed that obesity affects females and males in a sex-dependent manner. In addition, several works have demonstrated that parental obesity increases the risk to develop obesity, insulin resistance, diabetes, and reproductive disorders. Considering that intergenerational effects of obesity may occur in a sex-dependent manner, we studied male Wistar rat progeny (F1) obtained from mothers or fathers (F0) fed on a high-fat diet (HFD). Methods Five-week-old female and male Wistar rats were fed on a HFD (with 60% of calories provided by fat) for 18 weeks (F0). At the end of the treatment, animals were mated with young rats to obtain their progeny (F1). After weaning, F1 animals were fed on standard chow until 18 weeks of age. Body weight gain, fasting plasma glucose, insulin and leptin levels, glucose tolerance, insulin sensitivity, and adiposity were evaluated. In addition, beta-cell expression of nuclear p16 was assessed by immunofluorescence. Results and conclusions HFD altered plasma fasting glucose, insulin and leptin levels, glucose tolerance, adiposity, and beta-cell expression of p16 in F0 rats. Particularly, HFD showed sexual dimorphic effects on body weight gain and insulin sensitivity. Moreover, we observed that parental HFD feeding exerts parental-sex-specific metabolic impairment in the male progeny. Finally, parental metabolic dysfunction could be in part attributed to the increased beta-cell expression of p16; other mechanisms could be involved in the offspring glucose homeostasis.